1996
DOI: 10.1080/09540129650125966
|View full text |Cite
|
Sign up to set email alerts
|

Coping and social support as determinants of quality of life in HIV/AIDS

Abstract: Coping, social support and quality of life (QOL) were examined in 120 HIV+ people (mean age = 37). The sample came from ambulatory clinics and drop-in centres in Toronto: 29% had AIDS, 35% were HIV symptomatic, and 35% were asymptomatic. Information was gathered from self-administered questionnaires. Respondents had good levels of social support and used a variety of coping strategies. Their scores on the behavioural and subjective measures of QOL were somewhat below average. The illness-related measure indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
129
3
10

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(154 citation statements)
references
References 0 publications
10
129
3
10
Order By: Relevance
“…This finding is significant, as numerous studies have linked social support to physical health and management of HIV. For example, Friedland et al, (1996) found that emotional support was a statistically significant factor in determining quality of life for individuals living with HIV, and note that support services that "bridge the gap between informal and formal" (e.g., a camp experience) may be particularly beneficial (p. 28). Similarly, Ashton et al reported that satisfaction with social support was linked to a lower level of progression of HIV-related health symptoms (2005); Bekele et al (2013) found that perceived social support directly affected both physical and mental health, as well as mediating depressive symptoms; and Clingerman (2004) found that social support provided by friends was positively linked to health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding is significant, as numerous studies have linked social support to physical health and management of HIV. For example, Friedland et al, (1996) found that emotional support was a statistically significant factor in determining quality of life for individuals living with HIV, and note that support services that "bridge the gap between informal and formal" (e.g., a camp experience) may be particularly beneficial (p. 28). Similarly, Ashton et al reported that satisfaction with social support was linked to a lower level of progression of HIV-related health symptoms (2005); Bekele et al (2013) found that perceived social support directly affected both physical and mental health, as well as mediating depressive symptoms; and Clingerman (2004) found that social support provided by friends was positively linked to health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…For example, living with HIV affects both the type of social support needed, and the ability to access various forms of social support. Perceived social support, particularly emotional support, was found to be a significant factor in determining the quality of life for individuals living with HIV (Friedland et al, 1996). While the participants perceived the emotional support they received was of sufficient quality, they wished for a greater quantity of emotional support.…”
Section: Hiv Social Support and Well-beingmentioning
confidence: 99%
See 3 more Smart Citations